Effects of promoter and moisture on the deactivation of FSO3H catalyst in the synthesis of HFC-152a by hydrofluorination of acetylene - Lee, Young-Ho; Kim, Jae-Duck; Kim, Jaehoon; Kim, Hwayong; Lee, Youn-Woo (KOREAN INST CHEM ENGINEERS+, 2009)
The effects of promoter type and moisture on the catalytic activity of fluorosulfonic acid (FSO3H) as a liquid catalyst for the synthesis of HFC-152a by the hydrofluorination of acetylene were investigated. The catalyst containing SnCl4 as a promoter had a long catalyst lifetime compared to that without any promoter. It was also found that the composition of HFC-152a can be maintained at 100% for a long time by the control of the moisture content.